Impacts of some biostimulants on guar (Cyamopsis tetragonoloba L.) plants - El-Lethy, Safaa R. (2021)
The highest records of plant height and fresh and dry weights of leaves were recorded for plants treated with 300 mg/l nicotinamide followed by foliar treatment with 300 mg/l tryptophan. Fresh and dry weights of stems, number of pods/plant, fresh and dry weights of pods, pods yield, seeds yield, and straw yield followed the same trend. Total protein in guar seeds was significantly increased due to foliar treatment with tryptophan, especially in plants treated with 300 mg/l tryptophan, followed by plants treated with 300 mg/l nicotinamide. Total carbohydrates (mg/g dry wt.), total soluble sugars (mg/g dry wt.), total insoluble sugars (mg/g dry wt.), proline (μmol/g dry wt.), and total phenolic compounds (mg/g dry wt.) in the leaves followed the same trend.